2017
DOI: 10.1080/14613808.2017.1312323
|View full text |Cite
|
Sign up to set email alerts
|

Dalcroze meets technology: integrating music, movement and visuals with the Music Paint Machine

Abstract: New interactive music educational technologies are often seen as a 'force of change', introducing new approaches that address the shortcomings (e.g. score-based, teacher-centred and disembodied) of the so-called traditional teaching approaches. And yet, despite the growing belief in their educational potential, these new technologies have been problematised with regard to their design, reception, implementation and evaluation. A possible way to optimise the realisation of the educational potential of interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
(57 reference statements)
1
11
0
2
Order By: Relevance
“…Davidson et al (2001) proposed that teachers should employ movements and gestures to help pupils experience and understand the direction and intention of the music they are learning. Likewise, Nijs (2017) suggested integrating movementbased technologies to provide children with visual feedback, emphasizing embodied experiences in music making.…”
Section: Background: Teaching Young Musicians Performance Expressionmentioning
confidence: 99%
“…Davidson et al (2001) proposed that teachers should employ movements and gestures to help pupils experience and understand the direction and intention of the music they are learning. Likewise, Nijs (2017) suggested integrating movementbased technologies to provide children with visual feedback, emphasizing embodied experiences in music making.…”
Section: Background: Teaching Young Musicians Performance Expressionmentioning
confidence: 99%
“…Furthermore, effective feedback (Woody 2003) by the teacher (Hallam 1998), through recordings of students' performances (Hallam 2010;Juslin et al 2004;Woody 2000Woody , 2001 or computer software (Juslin et al 2006;Karlsson, Liljeström, and Juslin 2009) can be a useful tool for improving expressivity. Some scholars have suggested that children need physical movements to experience the music they are learning (Davidson, Pitts, and Correia 2001;Nijs 2017), while others have proposed that it might be helpful for teenage musicians to make some expressive decisions for themselves (McPhee 2011). Broomhead (2005Broomhead ( , 2006 found that teacher's enquiry encouraging students' initiative and providing problem-solving opportunities can facilitate expressive performance in secondary school choir rehearsals.…”
mentioning
confidence: 99%
“…A growing body of literature on music learning aligns with this multimodal perspective (Abril, 2011; Davidson, 2012; Gault, 2005; Juntunen & Hyvönen, 2004; Kerchner, 2014; Manifold, 2008; Nijs, 2017; Nijs & Leman, 2014, 2015). Furthermore, the multimodal of human interaction with music is confirmed in a large body of studies on music and movement (Gritten & King, 2011; Leman, 2007, 2016; Lesaffre et al., 2017).…”
Section: Introductionmentioning
confidence: 97%